Crossing Gender Boundaries: Exploring the Chain-Mediated Causal Role of Social Media Sharing in Shaping Interpersonal Networks and Enhancing Job Satisfaction - Xin Liu; Nan Qin; Xiaochong Wei (Behavioral Sciences)
The theoretical relationship between social media use and job satisfaction, especially concerning gender-specific mechanisms, remains a subject of ongoing debate in the literature. This divergence reflects our insufficient understanding of the complex relationships among gender, social media use, and job satisfaction. Drawing on Social Role Theory (SRT) and the Theory of Planned Behavior (TPB), this study utilizes 4651 valid samples from the 2020 China Family Panel Studies (CFPS) database to investigate how gender influences interpersonal relationships through social media sharing frequency, thereby enhancing job satisfaction. The findings indicate that women, compared to men, exhibit higher job satisfaction and more frequent social media sharing behavior. Moreover, the frequency of social media sharing positively affects job satisfaction by improving interpersonal relationships. This study employs a chain-mediated causal path analysis to delve into the causal relationships among gender, social media sharing frequency, and interpersonal relationships, effectively addressing previous limitations in handling multiple mediating effects. The findings not only provide new insights into the role of social media in the modern workplace but also offer empirical evidence and practical guidance for organizations on leveraging social media to foster employee relationships and enhance job satisfaction.